Careers for People Who like People: Interviews - Shorto, Russell; Keating, Edward; Boretz, Carrie (Brookfield, Conn. : Millbrook Press, 1992)
People working in a wide range of careers, including a day care worker, flight attendant, and hotel manager, describe the daily routine, benefits, and drawbacks of their jobs and the education and training they received.
Includes bibliographical references (p. 63) and index.
Keywords: Vocational guidance -- Juvenile literature; Employees -- Interviews; Interpersonal relations -- Juvenile literature; Vocational guidance; Occupations